Operation of an all-solar power system in Saudi Arabia. (February 2021) - Alraddadi, Musfer; Conejo, Antonio J.
Highlights: An all-solar electricity production mix makes sense in regions with high and stable solar irradiation, such as Saudi Arabia. An all-solar power system heavily relies on storage to cover nighttime hours. Simulation results for an all-solar power system in Saudi Arabia throughout one year are reported and discussed. The best option is generally a combination of CSP plants, PV plants and storage facilities. Abstract: This paper considers the operation of an all-solar electric energy system in Saudi Arabia, that is, a system which generation mix includes solely solar (PV and/or concentrated solar power (CSP)) and battery energy storage units (used to cover hours with no solar resource and hours beyond the CSP thermal storage capacity). We analyze the operation of this system using realistic data. These data pertain to the actual transmission system and the demand throughout the country in 2015. The Saudi Arabian power system exhibits a rather flat demand during both the summer and winter seasons (there are mostly two season in Saudi Arabia: winter and summer), being the peak demand for 2015 in these seasons 49 and 25 GW, respectively. Solar generation units and storage units are sized and sited using a fully-fledged capacity expansion model (not described in this paper). To comprehend the daily operation of such all-solar power system in Saudi Arabia throughout 2015, we analyze three cases in which the demand is served (i) using PV and storage units, (ii) using CSP and storage units, and (iii) using PV, CSP and storage units. We compare in detail the above three cases. We conclude that using an optimal combination of PV an CSP units results in minimum total (investment and operation) cost, minimum storage needs, and moderate solar energy spillage.